Human Exposure to Wireless Power Transmitter over Real Ground - Petra Rašić; Zoran Blažević; Dragan Poljak; Maja Škiljo (Journal of Communications Software and Systems)
The paper undertakes a comparative examination between a novel analytical methodology and a conventional numerical technique to analyze human exposure to electromagnetic fields emitted by a vertically positioned, electrically short antenna over a real homogeneous ground. In this investigation, the human body is represented as a vertically and horizontally positioned homogeneous cylinder, accounting for resonant and non-resonant frequencies, and corroborated with numerical simulations utilizing realistic human body models in FEKO software. The influence of the earth-air interface on real ground is considered by incorporating Fresnel’s reflection c oefficients. The analytical solution entails solving the Pocklington equation using the method of variation of constants, while the corresponding reflected field is determined through field integral evaluations. The innovative analytical approach adopts an approximate sinusoidal current distribution and analytical assessment of field integrals. The research demonstrates satisfactory alignment between these two methodologies and extends the previous analytical model by validating it with realistic human body models positioned over real ground, thereby increasing its complexity and practical applicability.